2022
DOI: 10.1002/jlb.4a1221-678rr
|View full text |Cite
|
Sign up to set email alerts
|

Methadone use is associated with increased levels of sCD14, immune activation, and inflammation during suppressed HIV infection

Abstract: Opioid use has negative effects on immune responses and may impair immune reconstitution in persons living with HIV (PLWH) infection undergoing antiretroviral treatment (ART). The effects of treatment with μ opioid receptor (MOR) agonists (e.g., methadone, MET) and antagonists (e.g., naltrexone, NTX) on immune reconstitution and immune activation in ART‐suppressed PLWH have not been assessed in‐depth. We studied the effects of methadone or naltrexone on measures of immune reconstitution and immune activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
1
1
0
Order By: Relevance
“…Our results aligned with previous reports examining the state of inflammation in virally suppressed PWH with IDU and OUD (9,28,32,33), showing increased expression of IL-6 (opioid use) (32), IL-8, sTNFR-II (methadone use) (28), and LBP, hsCRP, sTNFR-I, sTNFR-II, sCD14, sCD163 (heroin use) (28,32,33). In our study, plasma biomarkers were selected based on their reported association with inflammation (sTNFR-II, sTNFR-I, sCD25, TNFa, IL-6, IL-8, IL-1a, IL-1b, IL17A (Th17), IL-22 (Th17)) (34), cardiovascular disease (ICAM-I, VCAM-I, hsCRP), co-morbidities (IL-6, VCAM-I, ICAM-I, sTNFR-II, and sTNFR-I), monocyte activation and microbial translocation (sCD14, sCD163, iFABP, D-dimer, LBP) (32), HIV disease progression (MCP1/CCL2, sCD14) and mortality (sCD14) in the context of HIV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results aligned with previous reports examining the state of inflammation in virally suppressed PWH with IDU and OUD (9,28,32,33), showing increased expression of IL-6 (opioid use) (32), IL-8, sTNFR-II (methadone use) (28), and LBP, hsCRP, sTNFR-I, sTNFR-II, sCD14, sCD163 (heroin use) (28,32,33). In our study, plasma biomarkers were selected based on their reported association with inflammation (sTNFR-II, sTNFR-I, sCD25, TNFa, IL-6, IL-8, IL-1a, IL-1b, IL17A (Th17), IL-22 (Th17)) (34), cardiovascular disease (ICAM-I, VCAM-I, hsCRP), co-morbidities (IL-6, VCAM-I, ICAM-I, sTNFR-II, and sTNFR-I), monocyte activation and microbial translocation (sCD14, sCD163, iFABP, D-dimer, LBP) (32), HIV disease progression (MCP1/CCL2, sCD14) and mortality (sCD14) in the context of HIV.…”
Section: Discussionsupporting
confidence: 93%
“…Excessive T cell immune activation in virally suppressed PWH and its role in HIV disease progression are well known in the literature (6,20,27). One study reported that PWH with history of IDU and OUD, who were on oral methadone treatment, had greater levels of inflammation and immune activation than PWH with no history of OUD (11,28). Our study participants with OUD involved predominantly IDU with self-reported consistent opioid use for >90 days until the day of study enrollment and a positive opioid test in the UDS preceding the blood draw which was done on the enrollment day.…”
Section: Discussionmentioning
confidence: 99%
“…Many inflammatory factors were significantly elevated, including sCD14, sCD44, and LPS binding protein (LBP), consistent with previous reports [ 39 , 40 , 41 ]. Additionally, many complement components and platelet/coagulation-related factors including pro-platelet basic protein (PPBP) and platelet factor 4 (PF4/CXCL4), were elevated that have not been previously appreciated.…”
Section: Resultssupporting
confidence: 91%
“…Similarly, there is a wellestablished link between diet and systemic inflammation (29, 44) and substance use is known to affect diet and compromise nutrition, which is potentiated by factors including unstable housing (45). There are also mechanisms directly related to injecting drug use itself such as inflammatory and immunomodulatory effects of the drugs injected including methamphetamine, opioids and accompanying filler agents (46)(47)(48)(49)(50). Injury and infection related to injection site and injection practices can result from contaminated injecting equipment and/or the introduction of pathogens, foreign bodies and skin contaminants during the process of injecting (25,27,51).…”
Section: Discussionmentioning
confidence: 99%
“…Given the abovementioned differences in biomarker levels in PWID/HCV-as compared to those who did not report having injected drugs, we assessed the specific effect of viremic HCV infection on immune activation biomarkers exclusively in PWID populations. For these analyses, we compared 24 PWID/HCV-(median age [IQR] 37 [32,41], 33% female, Table 2) and 32 PWID with viremic HCV infection at baseline (PWID/HCV+; median age 39 [34,47]; 25% female) with a median [IQR] viral load of 202,229 [62,237 -1,987,626] copies/mL at enrolment. Generalised estimating equation models were used adjusting for age, sex and daily injecting drug use (Table 4, Figure 2).…”
Section: Viremic Hcv Infection Is Associated With Elevated Levels Of ...mentioning
confidence: 99%